Improving The Regulation Of Effective And Permanent Employment Of Youth In The Republic Of Uzbekistan - Zarifov Bobur (Genius Journals, 2025)
Today, the most important issue of effective employment of young people in labor activity is the issue of national and state importance. Because today, the composition of labor collectives in various sectors of our economy, the young men and women joining the ranks of entrepreneurs, will determine the development of Uzbekistan in the next 30-40 years.
Keywords: effective employment; development; green economy